2021
DOI: 10.1111/let.12433
|View full text |Cite
|
Sign up to set email alerts
|

Vauxiids as descendants of archaeocyaths: a hypothesis

Abstract: Archaeocyaths were one of the major animal groups contributing to the Cambrian Explosion. Despite an overall poriferan appearance of their hypercalcified skeletons, they exhibit a number of peculiar features such as the presence of septa and an absence of spicules. This sets archaeocyaths apart from general trends in early poriferan evolution. Fossils recently discovered from the early Cambrian Guanshan Lagerstätte of South China exhibit features typical for the suborder Archaeocyathina whilst possessing a sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Moreover, a recent study of fossils from the Guanshan Biota (Cambrian Stage 4) suggested that archaeocyaths of the suborder Archaeocyathina, to which D. translucidus also belong, are morphologically very close to vauxiid sponges [63]. The investigated Guanshan fossils can be comfortably assigned to either of these groups.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, a recent study of fossils from the Guanshan Biota (Cambrian Stage 4) suggested that archaeocyaths of the suborder Archaeocyathina, to which D. translucidus also belong, are morphologically very close to vauxiid sponges [63]. The investigated Guanshan fossils can be comfortably assigned to either of these groups.…”
Section: Discussionmentioning
confidence: 98%
“…5) [2]. These fossils were later diagnosed as the archaeocyath Dictyocyathus translucidus [60], a unique archaeocyath species whose skeleton is always preserved as moulds filled with sparitic cements [6163]. This exceptionality in archaeocyaths was previously attributed to originally aragonitic mineralogy in the skeleton [61,62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vauxiidae includes seven species of Vauxia and one species of Angulosuspongia, restricted to the Cambrian Burgess Shale-type fauna (Yang et al, 2017;Luo et al, 2020;Wei et al, 2021). Recently, Luo et al (2021) suggested archaeocyaths to be hypercalcified keratosan sponges, similar to Recent Vaceletia (Wörheide, 2008). Recognition of Spongiostroma as a keratosan demosponge (1) enhances recognition of fossil sponges, (2) clarifies longstanding confusion between vermiform fabric and clotted microbial fabrics (Pia, 1927;Johnson, 1961;Flügel, 2004;Kershaw et al, 2021), and (3) qualifies the suggestion that Spongiostroma is not a sponge (Neuweiler et al, online preprint).…”
Section: Introductionmentioning
confidence: 99%